Studi Persebaran dan Keterjangkauan Fasilitas Kesehatan di Kota Surakarta Tahun 2025 - Rajasya Ramadhan; Dewi Novita Sari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The availability of health facilities that are evenly distributed and easily accessible is an important factor in supporting public health services. This study aims to analyze the distribution and accessibility of healthcare facilities in Surakarta City in 2025 using a Geographic Information System (GIS) approach. The research employs a quantitative method with a census approach to all hospitals and community health centers in Surakarta City. Spatial data were obtained from the Geospatial Information Agency (BIG), Google Earth, and the Surakarta City Health Office, and then analyzed using spatial mapping and the Multiple Ring Buffer method on ArcGIS. The research results show that the distribution of hospitals has a clustered pattern and is concentrated in the Laweyan, Banjarsari, Jebres, and Pasar Kliwon sub-districts, while community health centers are more evenly distributed across all sub-districts. Accessibility analysis shows that the central area of Surakarta City has a higher level of hospital accessibility compared to the peripheral areas due to the concentration of healthcare facilities and a better transportation network. Although most areas are within the coverage of hospital services, there are still some areas in the northern, eastern, and southern parts of the city that are in the outermost reach zone. The research results show that the spatial distribution of healthcare facilities affects the level of accessibility to public health services in the city of Surakarta.